Buy now, pray later? Demystifying unrestrained spending in the age of BNPL - Furqan, Farhan; Pangaribuan, Christian Haposan; Tjhin, Santo; Luhur, Calista (Jurnal Siasat Bisnis, 2025)
Purpose – This research examines the relationship between intrinsic religiosity, financial literacy, intention to use BNPL, and their combined effect on the growing purchasing behavior of Jakarta’s youth.Design/methodology/approach – The study used a quantitative method with self-administered questionnaires provided to the target demographic in Jakarta. We also proposed a conceptual model that examines the connection between financial literacy and unrestrained purchasing behavior, intrinsic religiosity, and intention to use BNPL. Statistical techniques are applied to the collected data and for hypothesis testing. Findings – Initial results indicate that intrinsic religiosity and financial literacy are positively correlated, and research found a favorable correlation between the likelihood of unconstrained buying behavior and the intention to use BNPL.Research limitations/implications – Because a student sample was used and only a few respondents were included in the study, the findings may have wider applicability.Practical implications – The study emphasizes how important financial literacy is among young consumers, especially with relation to religious values and beliefs.Originality/value – While existing research rarely considers the specific influence of religious values, the novelty of the research lies in its focus on combining intrinsic religiosity and financial literacy when unrestrained buying behavior with Buy-Now-Pay-Later (BNPL) services.